Development of maize crop under the effect of saline water and organic matter (Colloquium Agrariae. ISSN: 1809-8215, 2020)
The objective of this work was to evaluate the use of organic matter in the development of corn irrigated with saline water. The experiment was carried out at the Agrarian Sciences Center of the Federal University of Alagoas. The experimental design was completely randomized in a 5 x 2 factorial scheme, with four replications, being the treatments: 5 levels of salinity (0.5 (control); 1.5; 3.0; 4.5 and 6.0 dS M-1) with presence and absence of organic matter. Saline solutions were prepared with NaCl and distilled water, and the formula: TSD (G L-1) = 0.64 x CEa was used. At 40 days after emergence, the plants were collected and analyzed for the number of leaves, leaf area, plant height, relative leaf chlorophyll index, shoot dry mass and root system dry mass. It was Found that all the variables studied in the maize crop were affected by the increase in salinity levels and that the soil decreased the effects of salinity when organic matter was added.